2022
DOI: 10.1038/s41467-022-29777-5
|View full text |Cite
|
Sign up to set email alerts
|

Fast encirclement of an exceptional point for highly efficient and compact chiral mode converters

Abstract: Exceptional points (EPs) are degeneracies at which two or more eigenvalues and eigenstates of a physical system coalesce. Dynamically encircling EPs by varying the parameters of a non-Hermitian system enables chiral mode switching, that is, the final state of the system upon a closed loop in parameter space depends on the encircling handedness. In conventional schemes, the parametric evolution during the encircling process has to be sufficiently slow to ensure adiabaticity. Here, we show that fast parametric e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
34
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 61 publications
(36 citation statements)
references
References 29 publications
1
34
1
Order By: Relevance
“…Some works have revealed that dynamically encircling EPs by adiabatically varying the parameters could lead to asymmetric mode transfer in a lossy waveguides system, thus realizing asymmetric mode/polarization converters. [134][135][136][137][138] Although the adiabaticity condition is still required for this system, the adiabatic approximation can be achieved via a fast parametric evolution along the boundary of the non-Hermitian Hamiltonian parameter space. Therefore, the mode-switching devices, requiring a small footprint, can be developed in the non-Hermitian regime.…”
Section: Topological Waveguide Arrays Toward Applicationsmentioning
confidence: 99%
“…Some works have revealed that dynamically encircling EPs by adiabatically varying the parameters could lead to asymmetric mode transfer in a lossy waveguides system, thus realizing asymmetric mode/polarization converters. [134][135][136][137][138] Although the adiabaticity condition is still required for this system, the adiabatic approximation can be achieved via a fast parametric evolution along the boundary of the non-Hermitian Hamiltonian parameter space. Therefore, the mode-switching devices, requiring a small footprint, can be developed in the non-Hermitian regime.…”
Section: Topological Waveguide Arrays Toward Applicationsmentioning
confidence: 99%
“…The study of non-Hermitian systems breaks the conventional scope of Hermitian Hamiltonians in closed systems, and also enriches the understanding about the quantum realm. [1] Once the gain or loss is introduced, exceptional points (EPs) are ubiquitous in non-Hermitian systems, such as those in optical microresonators, [2,3] coupled optical waveguides or cavities, [4][5][6] and fiber-based systems. [7,8] EPs are singularities where eigenvalues and the corresponding eigenvectors simultaneously coalesce, [9] and as one of the quintessential features in non-Hermitian physics, exhibit many topological properties that are not analogous to Hermitian systems.…”
Section: Introductionmentioning
confidence: 99%
“…[6,19,20] One of the most appealing phenomena is the state conversion when dynamically encircling an EP in a parameter space, exhibiting a chiral behavior. [21] This unique phenomenon has been demonstrated in myriad experiments of waveguides, [4,5,23,[25][26][27][28][29][30] evidencing the robustness to system perturbations including the form of the encircling loop and the device length. [22,23] The chiral switching is intriguing because the final state of system is solely determined by the encircling direction, regardless of the initial state.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations